Global analysis of next-generation utility-scale PV: Tracking bifacial solar farms. (15th May 2021) - Patel, M. Tahir; Ahmed, M. Sojib; Imran, Hassan; Butt, Nauman Z.; Khan, M. Ryyan; Alam, Muhammad A.
Highlights: Yearly energy gain of EW tracking over NS fixed-tilt 25–45% for latitude below 30°. EW tracking vs. NS tracking: 5–15% energy gain below 50° N/S and - 5 % above 50° N/S. EW tracking better than NS tracking for summer months and vice versa for winter. In-depth analysis on practicality of Sun-tracking vs. Power-tracking algorithms. Global analysis for minimum LCOE shows a worldwide optimum pitch of 2–3 m. Abstract: The bifacial gain of East-West vertical and South-facing optimally-tilted bifacial solar farms are well established. One wonders if bifacial gain and the associated levelized cost of energy (LCOE) may be further improved by tracking the sun. Tracking bifacial photovoltaics (PV) system has advantages of improved temperature sensitivity, enhanced diffuse and albedo light collection, flattened energy-output, and reduced soiling. Monofacial tracking already provides many of these advantages, therefore the relative merits of bifacial tracking are not obvious. In this paper, we use a detailed illumination and temperature-dependent bifacial solar farm model to show that bifacial tracking PV delivers up to 45% energy gain when compared to fixed-tilt bifacial PV near the equator, and 10% bifacial energy gain over tracking monofacial farm with an albedo of 0.5. An optimum pitch further improves the gain of a tracking bifacial farm. Our results will broaden the scope and understanding of bifacial technology by demonstrating global trends in energy gain for worldwide deployment.